The genome sequence of a tachinid fly, Tachina lurida (Fabricius, 1781) [version 1; peer review: 2 approved] - Matthew N. Smith; Steven Falk (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Tachina lurida (a tachinid fly; Arthropoda; Insecta; Diptera; Tachinidae). The genome sequence is 899.2 megabases in span. Most of the assembly is scaffolded into 6 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 17.3 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,127 protein coding genes.